A technical note on emerging combination approach involved in the onconanotherapeutics - Mohammad Kashif Iqubal; Harsimran Kaur; Shadab Md; Nabil A. Alhakamy; Ashif Iqubal; Javed Ali; Sanjula Baboota (Taylor & Francis Group, 2022)
Cancer is the second cause of mortality worldwide, and the currently available conventional treatment approach is associated with serious side effects and poor clinical outcomes. Based on the outcome of the exploratory preclinical and clinical studies, it was found that therapeutic response increases multiple folds when anticancer drugs are used in combination. However, the conventional combination of anticancer drugs was associated with various limitations such as increased cost of treatment, systemic toxicity, drug resistance, and reduced pharmacokinetic attributes. Hence, attempts were made to formulate nanocarrier fabricated combinatorial drugs (NFCDs) to effectively manage and treat cancer. This approach offers several advantages, such as improved stability, lower drug exposure, targeted drug delivery, low side effects, and improved clinical outcome. Hence, in this review, first time, we have discussed the recent advancement and various types of nano carrier-based combinatorial drug delivery systems in a different type of cancer and highlighted the personalized combinatorial theranostic medicine as a futuristic anticancer treatment approach.